KESIAPAN BUDAYA MASYARAKAT KOTA BATAM DALAM MENYAMBUT BATAM SEBAGAI KOTA WISATA - Dailami; Moh. Thamdzir; Dewi Aurora Mikasari (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2022)
Batam City is one of the largest cities in the Riau Islands Province which has a very strategic location, is located on international shipping lanes which have a very close distance, and is directly adjacent to the Singapore Strait and the Malayasia Strait. Batam City was built and developed with the establishment of the Batam Authority Agency based on Presidential Decree No. 41 of 1973 concerning the Batam Island Industrial Area which is currently the Batam City Concession Agency. As an Industrial City, Batam City is certainly a magnet for all Indonesian people to come as job seekers or just visit Batam City. Batam City, which in the early 1970s only had a population of 6000 people at this time has experienced very rapid growth according to the records of the Batam City Population and Civil Registry Office in 2020 the population of Batam City reached 1,157,882 people. Having a very strategic location supported by international standard facilities, at this time Batam City has been transformed into a Modern City so that it becomes one of the national strategic tourist destinations. The people of Batam City, which are heterogeneous with various tribes, religions, and cultures, have their charm for tourists. Malay, Javanese, Minang, Batak, Bugis, Palembang, and almost all ethnic groups in Indonesia are in Batam City. Malay culture which is synonymous with Islam is still very strong in Batam City which later became the root of local culture. The traditional house of cut pyramids, lemmang dance, zapin dance, traditional clothes, traditional weapons, and traditional Malay songs have their treasures that are always displayed in every cultural performance. Having rich and cultural roots that are always open to visitors, friendliness, courtesy, and modesty, and having very adequate infrastructure facilities are the main capital for the Batam City Government in developing Batam City tourism. So according to the records of the Batam City Tourism Office, in 2019 before the COVID-19 pandemic outbreak hit, the number of domestic tourist visits to Batam reached 6 million people and foreign tourists reached 1.9 million people.